2019
DOI: 10.3390/pr7110807
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Thermal Analysis of a Moving Spacecraft Subject to Solar Radiation Effect

Abstract: The impact of solar radiation on spacecraft can increase the cooling load, degrade the material properties of the structure and possibly lead to catastrophic failure of their missions. In this paper, we develop a computational model to investigate the effect of the exposure to solar radiation on the thermal distribution of a spacecraft with a cylindrical shape which is traveling in low earth orbit environment. This is obtained by the energy conservation between the heat conduction among the spacecraft, the hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Electrical torque peaked at roughly 19 N.m at full load and declined with reduced solar radiation for all algorithms. All the findings we get in this case study, like the findings of Fu et al (2016), Gadalla et al (2019)…”
Section: Case_2: Temperature Variationsupporting
confidence: 68%
“…Electrical torque peaked at roughly 19 N.m at full load and declined with reduced solar radiation for all algorithms. All the findings we get in this case study, like the findings of Fu et al (2016), Gadalla et al (2019)…”
Section: Case_2: Temperature Variationsupporting
confidence: 68%
“…Other studies, such as [7], have also explored the use of thermal data to determine the attitude of satellites. Furthermore, Gadalla Mohamed et al [3] demonstrated that the temperature difference between surfaces of a moving spacecraft can be significantly affected by its rotation, enabling the determination of the spacecraft's rotation rate.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of the space industry, the frequency of space activities, which include deep-space exploration, extravehicular activities and so on, will be higher and higher [1][2][3][4][5]. However, a lot of waste heat is generated when spacecraft are in working status, and solving the problem of the heat dissipation of spacecraft and equipment such as lunar probes and spacesuits has accordingly become the focus of the powerful countries in space exploration [6][7][8]. Space radiators and water sublimators are two types of necessary heat sinks for space cooling [6,9].…”
Section: Introductionmentioning
confidence: 99%